1995
DOI: 10.1128/mcb.15.2.918
|View full text |Cite
|
Sign up to set email alerts
|

A Deficiency of the Small GTPase rab8 Inhibits Membrane Traffic in Developing Neurons

Abstract: One of the major activities of developing neurons is the transport of new membrane to the growing axon. Candidates for playing a key role in the regulation of this intense traffic are the small GTP-binding proteins of the rab family. We have used hippocampal neurons in culture and analyzed membrane traffic activity after suppressing the expression of the small GTP-binding protein rab8. Inhibition of protein expression was accomplished by using sequence-specific antisense oligonucleotides. While rab8 depletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
87
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 33 publications
5
87
0
Order By: Relevance
“…These studies have identified Rab8 as a critical player in postsynaptic membrane trafficking and plasticity. Rab8 was proposed to mediate dendritic membrane trafficking and neurite outgrowth nearly a decade ago (27,67). These early studies, using neuronal dissociated cultures, suggested the involvement of Rab8 in early stages of the secretory pathway.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have identified Rab8 as a critical player in postsynaptic membrane trafficking and plasticity. Rab8 was proposed to mediate dendritic membrane trafficking and neurite outgrowth nearly a decade ago (27,67). These early studies, using neuronal dissociated cultures, suggested the involvement of Rab8 in early stages of the secretory pathway.…”
Section: Discussionmentioning
confidence: 99%
“…First, expression of activated Rab8 or Rabin8 promotes reorganization of actin and cell shape (Armstrong et al, 1996;PerĂ€nen et al, 1996;Hattula and PerĂ€nen, 2000;Chen et al, 2001; this report). Furthermore, mutant Rab8 causes cell death of transgenic Xenopus rods (Moritz et al, 2001) and depletion of Rab8 from primary neurons inhibits neurite outgrowth (Huber et al, 1995). Second, Rab8 interacts with FIP-2 (optineurin) that also modulates cell morphogenesis and links Rab8 to the huntingtin protein (Li et al, 1998;Hattula and PerĂ€nen, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Rab8 is essential in several areas of polarized neuronal transport as well as in plasma membrane trafficking in epithelial cells, and Rab8 siRNA knockdown prevents maturation of hippocampal neurons in culture (Huber et al, 1995;van Ijzendoorn et al, 2003;Ng and Tang, 2008). Studies now link Rab8 to a variety of different human diseases, including polycystic kidney disease, microvillus inclusion disease, and Bardet-Biedl syndrome, emphasizing the physiological importance of protein trafficking in human disease (Nachury et al, 2007;Ng and Tang, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic expression of dominant-negative Rab8 in Xenopus photoreceptor cells leads to rapid retinal degeneration, while depletion of Rab8 by siRNA in hippocampal neurons blocks morphological maturation through disruption of anterograde membrane traffic and impaired neurite outgrowth (Huber et al, 1995;Moritz et al, 2001). The Rab8 GEF, Rabin8, also plays a role in spine morphology as a phosphorylation-deficient Rabin8 mutant displays reduced spine head diameter (Ultanir et al, 2012).…”
Section: Discussionmentioning
confidence: 99%